Primary Biliary Cirrhosis-Specific Antimitochondrial Antibodies in Neonatal Haemochromatosis - Daniel S. Smyk; Maria G. Mytilinaiou; Tassos Grammatikopoulos; A. S. Knisely; Giorgina Mieli-Vergani; Dimitrios P. Bogdanos; Diego Vergani (Clinical and Developmental Immunology)
Background and Aim. Neonatal hemochromatosis (NH) is characterised by severe liver injury and extrahepatic siderosis sparing the reticuloendothelial system. Its aetiology is obscure, although it has been proposed as an alloimmune disease, resulting from immunological reaction to self-antigens (alloantigens) which the body recognizes as foreign. We studied an infant with NH and his mother whose sera contained antimitochondrial antibody (AMA), the hallmark of primary biliary cirrhosis (PBC). Material and Methods. To investigate the origin of AMA in the infant, we studied isotype distributions in serum from the mother and infant. Serum samples were obtained at diagnosis of NH, after liver transplantation (LT; age 1 month), and over the ensuing 17 months. Results. At NH diagnosis, infant and maternal serum contained AMA of the IgG isotype, predominantly of the G3 and G1 subclasses. AMA strongly reacted against the pyruvate dehydrogenase complex E2 subunit (PDC-E2), the major PBC-specific AMA autoantigen. Anti-PDC-E2 responses in both infant and mother declined over time, being present 2 months after LT (mother and child) and absent 10 months later (mother) and 17 months later (child). Conclusion. The association of maternally transferred IgG1 and IgG3 subclass AMA with the appearance of liver damage in an infant with NH may suggest a causal link between antibody and liver damage.